PERAN ZINK TERHADAP PENYAKIT GASTROENTERITI AKUT PADA ANAK DI DUNIA MENGGUNAKAN METODE SYSTEMIC LIRATURE - Wijayanty, Michelle Maria; Sulaeman, Fadel Reza; Irsyad, Muhammad Nur; July, July (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Acute gastroenteritis (GAE) is a significant global health problem, with children being the majority of cases, with high morbidity and mortality rates. Gastroenteritis is characterized by watery or almost watery diarrhea, accompanied by nausea and vomiting. In Indonesia, cases of AE in young children are increasing, partly due to a lack of awareness about hygiene. The pathophysiology of AE includes damage to the gastrointestinal mucosa due to infection by bacteria, viruses, or parasites, which causes increased fluid secretion and decreased absorption, leading to diarrhea. Several studies have found that zinc administration can shorten the healing time. This study aims to evaluate the role of zinc in the management of acute AE in children through a systematic literature review (SRB). The research method included a search for journal articles from 2015 to 2025 using the keyword "Acute Gastroenteritis in Children." A review of seven journals showed that zinc supplementation, at the recommended dose of 20 mg per day for children aged 6 months to 5 years, significantly reduced the duration and frequency of diarrhea, improved stool consistency, and increased intestinal resistance. Low zinc levels have been shown to be associated with diarrhea severity. Zinc contributes to the epithelialization of affected intestinal mucosa and could be a therapy to reduce unnecessary antibiotic use in cases of AE.